Analisis Putusan Hakim tentang Keabsahan Akta Pengikat Hibah terhadap Penghibahan Tanah Bangunan - Nisfa Lailah Sya’ban; Eva fauziah (Jurnal Riset Hukum Keluarga Islam, 2024)
Abstrak. Akta perikatan ‎hibah merupakan pendukung/perantara sebelum dibuatkannya akta hibah oleh PPAT. Namun dalam ‎prakteknya di lapangan akta pengikat hibah hadir sebagai akta pengesahan hibah. Penelitian ini merupakan penelitian hukum yuridis normatif dengan ‎teknik pengumpulan data dalam penelitian ini adalah penelitian kepustakaan atau library ‎research dan menggunakan sumber data yang mengutamakan data sukender dengan ‎mengoleh sumber-sumber dari putusan pengadilan, jurnal-jurnal dan buku. Hasil ‎penelitian ini menunjukkan bahwa pelaksanaan hibah di Indonesia dinyatakan sah harus ‎berdasarkan kepada akta hibah untuk dijadikan syarat dibuatnya sertifkat peralihan hak ‎di Kantor Pertanahan, sedangkan apabila pelaksanaan hibah didasari oleh akta pengikat ‎hibah tidak dibenarkan. ‎Konsep pertimbangan Hakim banding dalam terhadap putusan perkara didasarkan pada ‎peraturan Pasal 1676 KUHPerdata dan Pasal 1677 KUHPerdata jo Pasal 210 Kompilasi ‎Hukum Islam dan tinjauan hukum ‎positif terhadap putusan perkara rekonvensi berdasar pada Pasal 1682-1683 ‎KUHPerdata, dan PP Pasal 37 ayat 1 Nomor 24 Tahun 1997.‎ Abstract. The ratification of grants on land and buildings is based on the grant deed, but if the grant is based on a grant binding deed, it is not legally valid. However, in practice, in the field, the grant binding deed is present as a deed of grant ratification. The purpose of this study is to find out the provisions of the grant law and its implementation, to know the judge's considerations in deciding the case and how to review the positive law on the judge's consideration in granting the reconvention decision. This research is a normative juridical legal research with data collection techniques in this study is library research and uses data sources that prioritize consumer data by obtaining sources from court decisions, journals and books. The results of this study show that the implementation of grants in Indonesia declared valid must be based on the grant deed to be used as a condition for making a certificate of transfer of rights at the Land Office, while if the implementation of the grant is based on a deed of binding the grant is not justified. The concept of the appellate judge's consideration of the decision of the case is based on the provisions of Article 1676 of the Civil Code and Article 1677 of the Civil Code in conjunction with Article 210 of the Compilation of Islamic Law and the grantor is in accordance with the provisions of Article 1685 of the Civil Code and the deed of binding the grant based on Article 1320 of the Civil Code, and a positive legal review of the decision of the reconvention case based on Articles 1682-1683 of the Civil Code, and PP Article 37 paragraph 1 Number 24 of 1997.